Precision medicine in neonatology - Sara Silva Leite; Ana Cristina Barros; Catarina Ferraz Liz; Sofia Aires; Carmen Carvalho (Hygeia Press di Corridori Marinella, 2022)
Neonatal medicine has shown major advances in the past 50 years and this progress has allowed the increased survival, with less morbidity, of extremely preterm and critically ill neonates. Despite some conditions being unique to the neonatal population, neonatologists often have the need to adapt currently approved therapies from other populations. Certain diseases have such a wide variability in phenotype and response to drug therapy that it has become urgent to understand the underlying sources of variability, including genetics.  Precision medicine concerns the application of patient-specific profiles, through the determination and incorporation of genetic data, clinical and environmental factors, to determine individual risks and thus provide the most accurate point-of-care in disease management and prevention.  In this review, we discuss the current available knowledge concerning the applicability of precision medicine in different neonatology fields, such as newborn screening, neonatal nutrition, renal injury, hemodynamic assessment, lung pathology, epilepsy and neonatal pharmacology. To this end, the authors conducted a literature search of the PubMed® repositories, mainly using the terms "neonatology", "individualized medicine", "precision medicine", "personalized medicine", "genomics" and "metabolomics".  This article provides a summarized review of the research that is being conducted in numerous neonatal domains. But how can this new research be integrated in clinical practice?  Although some areas are already being used in neonatologists' daily activity, others, like genomics and metabolomics, seem to be limited to the investigational field. Even though the groundwork in such fields seems promising, its clinical utility and availability are still unknown. Further studies are needed, and the creation of a worldwide database, with the purpose of sharing patient data and outcomes, could be an important step for this evolving science.